Taxonomic Diversity of Fungi Associated with Some PCN Populations from Serbia - Violeta Oro; Jelena Bošković; Slobodan Milenković; Solveig Tosi (Pesticidi i Fitomedicina, 2012)
Increased content of pesticides in food chain resulted in using microorganisms asagents of biological control. The potato cyst nematodes (PCN) - Globodera pallida and G.rostochiensis belong to the group of the most important parasites - the quarantine organisms.The external and internal area of a cyst harbor numerous fungal and bacterial species.The aim of this study was to identify antagonistic fungi associated with some PCN populationsfrom Serbia. Fungal antagonists of potato cyst nematodes have not been previouslyinvestigated in our country. The diversity of PCN fungal antagonists is not reflected only atthe species level but also at the level of higher taxonomic categories.